2021
DOI: 10.1093/jacamr/dlab050
|View full text |Cite
|
Sign up to set email alerts
|

High level of HIV drug resistance informs dolutegravir roll-out and optimized NRTI backbone strategy in Mozambique

Abstract: Background HIV drug resistance (HIV-DR) is rising in sub-Saharan Africa in both ART-naive and ART-experienced patients. Objectives To estimate the level of acquired DR (ADR) and pre-treatment DR (PDR) across selected urban and rural sites in Southern Africa, in Mozambique. Methods We conducted two cross-sectional surveys among adult HIV patients (October 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Recent surveys among pregnant women in south rural Mozambique HIV-1 drug resistant mutation (DRM) was around 10% mainly due to NNNRTI and NRTI including NVP, EFV, 3TC, ABC, TDF [ 48 ]. In a survey of general population that included childbearing women as participants in south urban and central rural Mozambique [ 48 ] 83% were on tenofovir (TDF)/ lamivudine (3TC)/efavirenzes (EFV) and the pre-treatment drug resistance PDR (NNRTI) varied from 16.8% to 31.2% in south urban and central rural setting, respectively and mainly due to EFV/NVP drug resistance, mostly among pre-exposed. Acquired drug resistance (ADR) varied from 8.3% to 15.5% and the majority had NNRTI-NRTI dual resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent surveys among pregnant women in south rural Mozambique HIV-1 drug resistant mutation (DRM) was around 10% mainly due to NNNRTI and NRTI including NVP, EFV, 3TC, ABC, TDF [ 48 ]. In a survey of general population that included childbearing women as participants in south urban and central rural Mozambique [ 48 ] 83% were on tenofovir (TDF)/ lamivudine (3TC)/efavirenzes (EFV) and the pre-treatment drug resistance PDR (NNRTI) varied from 16.8% to 31.2% in south urban and central rural setting, respectively and mainly due to EFV/NVP drug resistance, mostly among pre-exposed. Acquired drug resistance (ADR) varied from 8.3% to 15.5% and the majority had NNRTI-NRTI dual resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired drug resistance (ADR) varied from 8.3% to 15.5% and the majority had NNRTI-NRTI dual resistance. The most common NRTI (ADR) was to 3TC/Emtricitabine and Abacavir [ 48 ]. These results support the probability of existence of drug resistance for the most first line drugs currently used for PMTCT reinforcing the need for individual HIV1-RNA and drugs resistance status assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Documented levels of pre-treatment (transmitted) drug resistance (PDR) for non-nucleoside reverse transcriptase inhibitors (NNRTI) for Low and Middle-Income Countries (LMICs) and across the world in 2015 showed increased rates over the 10% WHO threshold [11][12][13]. For Mozambique, a study in Maputo and Tete provinces also showed levels of NNRTI-PDR above the 10% threshold, and ADR for NNRTI and NRTI in 66% and 76% of the participants, respectively [14]. Altogether such studies were crucial when the country decided to transition to tenofovir/lamivudine/dolutegravir (TLD), and such results helped identify issues with emerging drug resistance [15].…”
Section: Introductionmentioning
confidence: 99%
“…Following ART scale-up, there have been global concerns over increasing levels of transmitted HIVDR [3]. Most studies have shown increasing levels of pretreatment HIV-1 drug resistance (PDR) mainly driven by non-nucleoside reverse transcriptase inhibitor (NNRTI) mutations [4,5], with a modelling study by Phillips et al, showing a benefit of changing first-line ART regimens in a setting of high NNRTI resistance [6]. This resulted in the World Health Organization (WHO) recommendation for use of dolutegravir (DTG) in all ART regimens [7], given DTG's better tolerability, less adverse effects, higher genetic barrier to resistance, and availability in a fixed dose combination with tenofovir (TDF) and lamivudine (3TC), i.e.…”
Section: Introductionmentioning
confidence: 99%